Promising best practices that lead to employment in vocational rehabilitation: Findings from a four-state multiple case study. - Del Valle, Roy; Leahy, Michael J.; Sherman, Susan; Anderson, Catherine A.; Tansey, Timothy; Schoen, Barbara (Journal of Vocational Rehabilitation, 2014)
The state-federal vocational rehabilitation (VR) program has been challenged to demonstrate the effectiveness of VR services provided to eligible consumers. State-federal VR agencies are under pressure to develop a foundation of evidence-based practices that lead to competitive employment outcomes for people with disabilities. This article provides a qualitative analysis of the organization structural elements and service delivery practices related to the provision of effective best practices that enhance employment outcomes for individuals with disabilities. Using a Consensual Qualitative Research (CQR) approach, a multi-stage qualitative analysis of four high performing state VR agencies was conducted to identify promising organizational and service delivery practices that facilitate employment outcomes. Twenty-nine practices were identified as being supportive of the successful outcomes of persons with disabilities being served by these agencies. The identified practices reflect unique and similar service patterns across the four VR agencies studied. Practices were divided into Promising Organizational Practices and Promising Service Delivery Practices. The culture of an organization is an important factor in the development and sustainability of innovative practices. Best practices reconsider traditional rehabilitation counselor roles and offer new methods for delivering services. Rigorous research and program evaluation are required to identify which practices will ultimately constitute evidence-based practices.